Impact of high resistivity transparent (HRT) layer in cadmium telluride solar cells from numerical simulation - Doroody C.; Rahman K.S.; Rosly H.N.; Harif M.N.; Haque F.; Tiong S.K.; Amin N. (American Institute of Physics Inc., 2023)
Cadmium sulfide; Cadmium sulfide solar cells; Efficiency; II-VI semiconductors; Sulfur compounds; Zinc compounds; Cadmium telluride solar cells; CdTe solar cells; Cell capacitance; Conventional design; Increased temperature; Optimal parameter; Recombination loss; Transparent conductive oxides; Cadmium telluride